El micro comercio y su contribución al desarrollo familiar de los comerciantes del mercado 10 de noviembre en el primer trimestre del 2019 - Ponce Olalla, Lida Jacqueline (2019)
The present project arises with the purpose of establishing the contribution that micro-commerce has in the development of families, with the general objective of: Analyzing micro-commerce and its contribution to family development of market traders November 10 in the first quarter of the year 2019. For which it is considered to use the descriptive study and in this way to determine demographic characteristics of the merchants as well as singularities of the activity such as investment, generation of resources, beneficiaries, satisfaction of needs, for which the researchers used the survey as the information collection technique that was processed using the statistical software SPSS for the representation of the information in tables and figures, for the easy understanding of the information gathered with which it has been established that despite the income received these have allowed them to cover basic needs tant or of them as of their relatives, since with these they can acquire the necessary food, cover expenses of education, housing, health and clothing of the relatives who are dependent on the micro merchants. Key words: micro commerce, family economic development, market November